(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2024)
We shall never truly know to what extent an encounter, a person, a book or a life situation has influenced our destiny and becoming. If not for the awakening of self-consciousness, that imago, transformation and becoming of each of us, was prepared long before it occurred, through providential encounters with those who guided our formation, without us being aware of this thing. The awareness of the moment in which the assumed construction of one’s own status begins coincides with the understanding of the importance of the people met by the will of destiny and without whom one’s own becoming would not have been possible. Only then, reliving the stages of life in the mind, the image of the mentors takes shape, enveloped in an overwhelming gratitude, in a deep and ever-growing admiration for their way of being, of thinking, of working. Although the tumult of life and daily challenges do not always leave room for prolonged memories, it is always a moral obligation to commemorate those who supported us morally and professionally at the outset of our carrier. Evoking the teacher and scientist Ligia Bârzu is both a privilege and a moral duty. A privilege because she was successively our teacher, guide, and colleague. A moral duty as a natural part of our existence because the cultivation of memory is, equally, a recuperative gesture for those who have left and a purifying one for those who remain. We owe to professor Ligia Bârzu not only a part of our personal and scientific development, but also the inspired example of a dignified, assumed, and honest life.